Pengembangan LKPD Menulis Teks Prosedur Berbasis Project Based Learning - Dedi Satriawan (LPPM STKIP PGRI Bandar Lampung, 2024)
The aim of this research is to develop LKPD teaching materials for writing project-based procedural texts, determine whether this program is feasible and how effective it is for participants in class XI high school. This type of research is research and development (R&D). The method used in the three high schools (SMA) in Bandar Lampung which were used as research sample data was by using observation, interviews and questionnaire distribution methods. Products are tested on students and validated by experts and peers. The results of the research show that the LKPD for Writing Procedure Texts Based on Project Based Learning was successfully developed. Through validation from material experts, media experts, and practitioners, it was stated that the LKPD as a whole was